2001
DOI: 10.1152/ajpgi.2001.280.6.g1163
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 expression and regulation in rat enteric glial cells

Abstract: As yet, little is known about the function of the glia of the enteric nervous system (ENS), particularly in an immune-stimulated environment. This prompted us to study the potential of cultured enteroglial cells for cytokine synthesis and secretion. Jejunal myenteric plexus preparations from adult rats were enzymatically dissociated, and enteroglial cells were purified by complement-mediated cytolysis and grown in tissue culture. Cultured cells were stimulated with recombinant rat interleukin (IL)-1beta, IL-6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 53 publications
(69 reference statements)
4
107
1
2
Order By: Relevance
“…In addition, transcripts encoding IL-1␤ and IL-6, which were increased during DSS-induced colitis, have been shown to regulate cytokine production by enteric glial cells. 51 Although no differences were observed in basal intestinal permeability to FITC-conjugated dextran, the possibility remains that permeability differences might be present under inflammatory conditions. It has been proposed that PrP C may function as an antimicrobial peptide.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, transcripts encoding IL-1␤ and IL-6, which were increased during DSS-induced colitis, have been shown to regulate cytokine production by enteric glial cells. 51 Although no differences were observed in basal intestinal permeability to FITC-conjugated dextran, the possibility remains that permeability differences might be present under inflammatory conditions. It has been proposed that PrP C may function as an antimicrobial peptide.…”
Section: Discussionmentioning
confidence: 95%
“…The divergent effects of type 1 (inflammatory) and type 2 (immunomodulatory) cytokines on EGC proliferation could have pathophysiological relevance since the nature of the cytokine profile during Crohn's disease, a human chronic IBD, shifts from a type 2 response in early lesions to a type 1 response in chronic lesions (Desreumaux et al, 1997). Moreover, Rü hl et al (2001a) have demonstrated that EGCs produce IL-6, similar to astrocytes (Van Wagoner and Benveniste, 1999). Indeed, in vitro stimulation of EGC cultures with IL-1␤ induces IL-6 mRNA expression, and stimulation of EGCs with IL-6 induces a dose-dependent suppression of IL-6 expression.…”
Section: Implication Of Egc In Inflammatory Andmentioning
confidence: 99%
“…No gastrointestinal disorder has been reported linked to glial defect yet, most probably because subtle changes in glial function might be involved in the etiopathogenesis of enteric disorders. Crohn's disease with neuroinflammation and neurodegeneration components may be associated with EGC alteration [23][24][25] . Indeed EGC interact with enteric neurons, endothelial cells, immune cells and the intestinal epithelium; all these factors can contribute to the pathogenesis of Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…EGCs are an active part of an intestinal network system essential for a healthy and functional gut [23,26,27] . The role of EGC in Crohn's and other enteric diseases is not well studied and this is the first report that attempts to unravel interaction between an intestinal pathogen and EGC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation